Adaptive Curriculum Transformation to Realize Rights-Based Inclusive Education Services within the Pesantren Institutional Ecosystem - Zaki Zamzami (JURNAL ILMIAH GEMA PERENCANA, 2026)
This policy study is prompted by the suboptimal inclusive education services in Islamic boarding schools (pesantren), leaving students with disabilities marginalized due to rigid and exclusive traditional curricula. The core issue lies in the dominant charity-based care paradigm, which hinders the fulfillment of students' rights, particularly concerning the modification of classical text (kitab kuning) standards and diploma legality. The policy analysis methodology utilizes the Urgency, Seriousness, and Growth (USG) method to prioritize issues, alongside fishbone diagrams for root cause mapping. Various policy alternatives are evaluated using William N. Dunn’s criteria, encompassing effectiveness, efficiency, adequacy, equity, responsiveness, and appropriateness. Findings indicate that the limited adaptive curriculum is the most critical barrier, rooted in partial disability theology internalizations and cultural resistance to deconstructing classical texts. The discussion emphasizes integrating Universal Design for Learning (UDL) and Individualized Education Programs (IEP) as technical bridges that preserve the sanctity of pesantren scholarship. The conclusion asserts that ministerial-level policy intervention is urgent to resolve administrative uncertainties. The primary recommendation urges the Minister of Religious Affairs to promptly issue a Directorate General of Islamic Education Decree regarding Adaptive Curriculum Guidelines and Inclusive Graduation Standards. This regulation is expected to provide legal legitimacy for workload modifications, ensure diploma recognition, and transform pesantren into a just, rights-based educational ecosystem for all students without exception.